2001
DOI: 10.1007/s002530100614
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of green fluorescent protein gene into phenol-degrading Alcaligenes faecalis cells and their monitoring in phenol-contaminated soil

Abstract: Alcaligenesfaecalis (CCT 7145) was isolated from an Amazonian soil sample after an enrichment process to select for phenol-degrading microorganisms. The isolate was labeled with the green fluorescent protein (gfp) gene. The gfp-transformed cells were easily detected using a hand-held UV transilluminator and their taxonomy was confirmed by 16S rRNA sequencing. Polymerase chain reaction (PCR) and Southern blot analyses confirmed that the gfp gene was integrated into the chromosome. The addition of the gfp marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…To some extent, this result confirms previous studies which showed that fluorescence can be used to monitor GEMs (Leff and Leff 1996;Bastos et al 2001).…”
Section: Resultssupporting
confidence: 91%
“…To some extent, this result confirms previous studies which showed that fluorescence can be used to monitor GEMs (Leff and Leff 1996;Bastos et al 2001).…”
Section: Resultssupporting
confidence: 91%
“…Alginate is the most commonly investigated carrier for bioremediation applications, and has been used with numerous contaminants including chromium, cresol, nitrate, pentachlorophenol, phenanthrene, phenol, phosphate, and 2,4,6-trichlorophenol. 10,28,73,75,87,141,166,206,250 Alginate may also have potential for delivery of naked DNA directly into the environment for the purpose of gene bioaugmentation, 1 which is discussed in a later section.…”
Section: Bioaugmentation With Encapsulated Microorganismsmentioning
confidence: 99%
“…The capsule matrix can buffer the introduced microorganisms against pollutant toxicity in the environment. 10,149 Additionally, substrates or C compounds can be added to the capsule to confer an advantage to the embedded inoculant; 236 however, Duquenne et al…”
Section: Bioaugmentation With Encapsulated Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capsule matrix can buffer against environmental stress and pollutant toxicity (5,23) and protects the inoculum from predation and indigenous microorganisms (29) while allowing the diffusion of gases and liquids (37). Carrier materials to encapsulate cells for biodegradation include, among others, alginate, gelatin, and -carrageenan gel (36).…”
mentioning
confidence: 99%